A disposable chemical heater and dry enzyme preparation for lysis and extraction of DNA and RNA from microorganisms. Issue 14 (11th March 2016) - Buser, J. R.; Zhang, X.; Byrnes, S. A.; Ladd, P. D.; Heiniger, E. K.; Wheeler, M. D.; Bishop, J. D.; Englund, J. A.; Lutz, B.; Weigl, B. H.; Yager, P.
Abstract : A simple dry enzyme and sample heating approach for point-of-care molecular diagnostic devices is demonstrated. Abstract : Sample preparation, including bacterial lysis, remains a hurdle in the realization of complete point-of-care tests for many pathogens. Here, we developed a sample preparation methodology for enzymatic lysis and sample heating for low-resource, point-of-care applications. We show an instrument-free chemical heater system for rapid lysis of a Gram-positive bacterium ( Staphylococcus aureus ) and an RNA virus (human respiratory syncytial virus) using a dried lysis enzyme mixture (achromopeptidase) for S. aureus . After a lysis step (<1 minute), lysis enzymes are heat deactivated (<5 minutes) using a simple disposable chemical heater. We demonstrated that both DNA and RNA in the heat-treated sample could be directly amplified without purification, even in the presence of a clinically-obtained human nasal sample. This simple approach to dry enzyme storage and sample heating is adaptable to many applications where samples need to be lysed, including use in low-resource laboratories and in single-use or cartridge-based point-of-care diagnostic devices.